Karakteristik Minimmum Quantity Lubrication Dengan Pelumas Nabati Terhadap Jarak Potong dan Flank Wear Pahat Carbide - Priyahapsara, Istyawan (Institut Teknologi Dirgantara Adisutjipto, 2016)
Maching using coolant causing environmental problems. Improper coolant waste handling can damage surrounding environment. In Minimum Quantity Lubrication (MQL) there are lubrication that can reduce friction force between tool and working material thereby can reduce the rate of temperature rise, and can impove tool lifeThe purpose of this research is to analyse the use of vegetable oil lubricant as alternative MQL lubricant on cutting distance and flank wear of the work material.This research using vegetable oils consisted of palm oil, coconut oil, soybean oi, and maize (corn) oil. Those vegetable oils were tested their physical properties to be compared with ester oil especially the kinematic viscosity and flash point properties. Turning process were done until flank wear reach 0.3 mm.Soy beam are choose as the best vegetable oil used as MQL. Compared with dry, MQL soy beam produce longer cutting distance. Compared with wet and MQL ester oil, soy beam oil produce shorter life tool.